The Gaia RVS benchmark stars: I. chemical inventory of the first sample of evolved stars and its Rb NLTE investigation - Caffau, Elisabetta; Bonifacio, P.; Korotin, S. A.; François, P.; Lallement, R.; Pinto, A. M. Matas; Matteo, P. Di; Steffen, M.; Mucciarelli, A.; Katz, D.; Haywood, M.; Chemin, L.; et al. (Astronomy and astrophysics, 2021)
Context. The Radial Velocity Spectrometer (RVS) on board the Gaia satellite is not provided with a wavelength calibration lamp. It uses its observations of stars with known radial velocity to derive the dispersion relation. To derive an accurate radial velocity calibration, a precise knowledge of the line spread function (LSF) of the RVS is necessary. Good-quality ground-based observations in the wavelength range of the RVS are highly desired to determine the LSF. Aims. Several radial velocity standard stars are available to the Gaia community. The highest possible number of calibrators will surely allow us to improve the accuracy of the radial velocity. Because the LSF may vary across the focal plane of the RVS, a large number of high-quality spectra for the LSF calibration may allow us to better sample the properties of the focal plane. Methods. We selected a sample of stars to be observed with UVES at the Very Large Telescope, in a setting including the wavelength range of RVS, that are bright enough to allow obtaining high-quality spectra in a short time. We also selected stars that lack chemical investigation in order to increase the sample of bright, close by stars with a complete chemical inventory. Results. We here present the chemical analysis of the first sample of 80 evolved stars. The quality of the spectra is very good, therefore we were able to derive abundances for 20 elements. The metallicity range spanned by the sample is about 1 dex, from slightly metal-poor to solar metallicity. We derived the Rb abundance for all stars and investigated departures from local thermodynamical equilibrium (NLTE) in the formation of its lines. Conclusions. The sample of spectra is of good quality, which is useful for a Gaia radial velocity calibration. The Rb NLTE effects in this stellar parameters range are small but sometimes non-negligible, especially for spectra of this good quality.
Gesehen am 23.09.2021